2018
DOI: 10.1108/pijpsm-12-2017-0155
|View full text |Cite
|
Sign up to set email alerts
|

Hot spots of mental health crises

Abstract: Purpose A strong body of research has established the concentration of crime in a small number of street segments or “hot spots” throughout urban cities, but the spatial distribution of mental health-related calls for services is less well known. The extent to which these calls are concentrated on a small number of street segments, similar to traditional crime calls for service is understudied. The purpose of this paper is to examine the concentration of mental health calls and the spatial distribution of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…In total, this subset includes 3,262 calls for service, thus comprising 0.89% of all calls made to the Barrie Police Service between 2014 and 2019. This finding is within the 0.50 to 3.48% range of previous work (Hodgkinson & Andresen, 2019;Vaughan et al, 2016White & Goldberg, 2018).…”
Section: Study Jurisdiction and Datasupporting
confidence: 88%
See 3 more Smart Citations
“…In total, this subset includes 3,262 calls for service, thus comprising 0.89% of all calls made to the Barrie Police Service between 2014 and 2019. This finding is within the 0.50 to 3.48% range of previous work (Hodgkinson & Andresen, 2019;Vaughan et al, 2016White & Goldberg, 2018).…”
Section: Study Jurisdiction and Datasupporting
confidence: 88%
“…Relative to jurisdictions in previous research on the spatial concentration of PwPMI calls, Barrie is the smallest jurisdiction based on land area (Vaughan et al, 2016(Vaughan et al, , 2019White & Goldberg, 2018), has the fewest number of dissemination areas (Hodgkinson & Andresen, 2019;Vaughan et al, 2016Vaughan et al, , 2019see Vaughan et al, 2018 for excpetion), and the fewest number of street segments (Hodgkinson & Andresen, 2019).…”
Section: Units Of Spatial Analysismentioning
confidence: 82%
See 2 more Smart Citations
“…These findings have been found for crime generally (e.g. see Weisburd, 2015;Weisburd, Hinkle, Famega, & Ready, 2011) and also with specific types of crime such as drug markets (Weisburd & Green, 1995;Weisburd & Mazerolle, 2000), juvenile crime (Weisburd, Morris, & Groff, 2009), gun violence (Braga, Papachristos, & Hureau, 2014), and mental health related calls (White & Goldberg, 2018). Furthermore, a recent study found that individuals who live in violent crime hot spots are more likely to have depression and/or PTSD ; see also .…”
Section: Geographic Contextmentioning
confidence: 71%